HEMATOLOGICAL PARAMETERS IN CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA AMONG SUDANESE - May Mohammed Ali; Abu Elgasim Abass Awad Elkareem; Mugtaba Ahmed Abdelrazig; Elshazali Widaa Ali ("Conference on Universal Science Research 2023", 2024)
Acute lymphocytic leukemia (ALL) is white blood cells disorders of lymphoid precursor cells in bone marrow, blood and extramedullary sites; it has two peaks, the childhood peak and the peak above age of forty. The study aimed to determine hematological parameters among Sudanese child patients with ALL. Fifty patients attended flowcytometry laboratory (Khartoum- Sudan), during the period from July 2016 to January 2017 recruited in this study. Venous blood samples were collected from each patient in EDTA blood container and then analyzed by automated hematology analyzer for measurement of hematological parameters and flowcytometer to identify ALL types and subtypes. Data were analyzed by statistical package for social science (SPSS) computer software program. The sex of patients revealed that 36 (72%) males and 14(28%)females (male female ratio was 2.6:1). The patient age ranged from 1 to 11 years, with mean age (5.16). B-ALL represent 45 (90%) of cases while T- ALL represents 5 (10%) of cases. The B- ALL subtypes identified were early pre B- ALL 31cases, pre B- ALL 10 cases, common B- ALL 3cases and Burkitt’s type one case; while T- ALL subtype identified was cortical T-cell ALL 5cases. The complete blood count of patients as follows (Mean±SD): TWBCs (69.92±141.206X109/L), RBCs (2.80±0.8817X10¹²/L), PLTs (58.62±62.8171X109/L.), Hb (8.08±2.415 g/dl), and blast (73.56 % ±18.11%). This study concluded that ALL was common in males than females. B- ALL was more frequent than T- ALL; among B- ALL subtypes; early B-ALL was the most prevalent, while T- ALL subtype was cortical. Total white blood cells count was significantly higher inpatients with T-ALL than B-ALL. Hyperleucocytosis was observed in 14% of patients, 80% of patients were anemic and 88% of patients were thrombocytopenic.